Enhancing forced convection solar collector efficiency through structural optimization: A comparative study of U-Tube, flow-guiding baffle and S-channel configurations - Guoshun Yuan; Hongzhou Zhang; Heying Chu (Results in Engineering)
Aiming at the problems of low heat exchange efficiency of forced convection solar collectors and the existence of flow dead zones at the tail of vacuum tubes, this article, starting from the internal structure, proposes three new structures: ''U-tube type'', ''flow-guiding baffle type'' and ''S-channel type''. The corresponding three-dimensional mathematical model was established using SOLIDWORKS software, and then the internal flow and heat transfer characteristics of the solar collector under the new and old structures were simulated using Fluent software.The results show that there is a flow dead zone at the tail of the vacuum tube of the solar collector under the conventional structure, which is not conducive to convective heat transfer, resulting in a slow outlet heating rate and low heat exchange efficiency. Three new structures of solar collectors have solved the problem of dead zones inside the vacuum tubes and enhanced the convective heat transfer between water and the inner walls of the vacuum tubes. Among them, the S-channel configuration exhibited the best performance. Compared to the conventional configuration, it achieved average Nusselt number enhancements of 255.99 % and 163.39 % at vacuum tube counts of 4 and 12, respectively. The outlet temperature increased by 4.38 % and 7.80 %, while the inlet-outlet temperature difference reached significantly higher values of 20.81 K and 33.56 K.